Problematika Penerapan Kurikulum Merdeka terhadap Pembelajaran Bahasa Arab di Madrasah Tsanawiyah Muslimin Indonesia Center (MIC) Samarinda - Munawarah, Munawarah; Munawwir, Ahmad; Chalik, Sitti Aisyah; Al-Qifari, Abudzar (Shaut al Arabiyyah, 2026)
The purpose of this study is to determine the implementation of the Independent Curriculum in Arabic language learning at MTs Muslimin Indonesia Center, to identify emerging problems, and to provide solutions or recommendations to address these obstacles. This study uses a descriptive qualitative research method. The research approach includes a pedagogical approach, and a social. Data sources include the principal, Arabic language teachers, and the vice principal for curriculum. Data collection techniques consist of observation, interviews, and documentation, using observation guidelines, interview guidelines, and documentation checklists. Data analysis follows the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. The results show that the implementation of the Independent Curriculum still faces various obstacles, such as teachers' lack of understanding of the terms and concepts of the new curriculum, suboptimal preparation of learning tools, limited learning resources, minimal use of technology, and learning time that does not match the number of hours stipulated in the curriculum. However, in terms of assessment, no obstacles were found for Arabic language teachers. To address these challenges, this study recommends increasing teacher training and mentoring, as well as optimizing the implementation of project-based learning to improve students' Arabic language competency. Furthermore, proposed solutions include improving Arabic reading and writing habits, increasing the stock of textbooks, adjusting learning schedules.